Translational microsurgery. A new platform for transplantation research - Eiji Kobayashi; Junko Haga (Acta Cirúrgica Brasileira, 2016)
ABSTRACT PURPOSE: Clinical microsurgery has been introduced in many fields, while experimental microsurgery has the cross-disciplinary features of the sciences and techniques for growth of medicine, pharmacology, veterinary, engineering etc. Training protocol, proposing a new name as Translational Microsurgery, was introduced. METHODS: Reconstructive skills of hepatic artery in pediatric living donor liver transplantation were summarized. Ex vivo training protocol using artificial blood vessel for surgeons was proposed. RESULTS: Clinical microsurgery requires anastomosis with delicate arteries and limited field of view. Our training protocol revealed that the relation between the score and speed was seen, while not all the surgeons with enough experience got high score. This training led to muster clinical skills and to apply excellent experimental works. CONCLUSIONS: Our microsurgical training protocol has been planned from the points of clinical setting. Training for vascular anastomosis led to rodent transplantation models. These models were used for immunology and immunosuppressant research. Microsurgical techniques led to master catheter technique and to inject various drugs or gene vectors.